IDENTIFIKASI MAKROZOOBENTHOS DI TUKAD BAUSAN, DESA PERERENAN, KABUPATEN BADUNG, BALI - Suartin, Ni Made; Sudatri, Ni Wayan; Pharmawati, Made; Raka Dalem, A. A. G. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
A macrozoobenthos study was conducted at Bausan River, Pererenan village, Badung regency, Bali between September and December, 2006. There were six sampling stations were determined purposively. At each station, five unit of square plots of 40 cm x 40 (in maximum solum depth) samples were taken. The result showed that there were seventeen species of macrozoobenthos were found. There was no protected species found in this study. The macrozoobenthos had 2,28 level of index diversity. This indicated that the ecosystem at this area was in a stable condition with a medium level of macrozoobenthos diversity.
Keywords: macrozoobenthos, Bausan River, Diversifikasi index